Registers of Loss : PhotoTalking with the Baobab Trees of Nyatate - Mwanaka, Tendai R. (Book collections on Project MUSE., 2021)
"The baobab trees are ancient trees, some might be thousands years old, imagine the people who have stayed in these dwellings, who have ate the fruits of these trees, who have used its leaves as relish(we create mashed okra relish with baobab leaves), the ailments treated by its buck....every part of this succulent tree is useful. In this photo journey I learned a lot more about these beautiful souls: they have a tendency to create musical lines, mostly linear, it's like one tone starting it, fading and letting the next tone to take over and this will fade and let another tone to take over, such that you can see the lines, how they conjoin to create music beyond human understanding. And most of the Baobabs, I realized, inhabit the same place in numbers, and usually they are on high grounds, like Gods who love elevated dwellings, and they look down upon other small humans (small trees, humans etc...), but there are also some singular baobabs that inhabit lower grounds and most of these are solitary and from my memory growing up here, these don't bear fruits. And whilst I was photographing the Baobabs several story strands in my head converged around one far much more important issue, the issue of Climate Change and Global Warming. In Registers of Loss I encourage working together as human beings to arrest Global warming and climate change the way the baobabs work together to communicate in linear notes, or in community thoughts."--